Pedagogická komunikace se zaměřením na výuku informačních techologií - Kovařík, Ivan; Ivan Kovařík (České vysoké učení technické v Praze, 2020)
Bakalářská práce se věnuje pedagogické komunikaci ve výuce informačních tech-nologií se zaměřením na využití učebních otázek v práci lektora vzdělávání dospělých. Cílem práce je na základě předložených případových studií sestavit doporučení pro pedagogickou komunikaci se zaměřením na výuku informačních technologií, pro potřebu vybrané firmy. Praktická část je zpracována kvalitativním výzkumem metodou případových studií. V závěru práce jsou uvedena doporučení pro pedagogickou komunikaci práce lektora informačních technologií, která vyplynula z praktické části.

The bachelor's thesis deals with pedagogical communication in teaching infor-mation technology with a focus on the use of questions by the lecturer in adult education. The aim of the work is to make recommendations for pedagogical communication based on the presented case studies, with a focus on teaching information technology to meet the needs of a specific company. The practical section encompasses qualitative research using the case studies method. The conclusion offers recommendations for pedagogical communication in the work of an information technology lecturer based on the results of the practical part of the thesis.
Pedagogical communication with a focus on teaching information technology
Keywords: Pedagogická komunikace; učební otázky; komunikace; vzdělávání dospělých; Pedagogical Communication; Learning Questions; Communication; Adult Education